A longitudinal investigation on the effects of sodium and potassium intake have on the development of hypertension and abdominal obesity from childhood to young adulthood amongst Ellisras rural population, South Africa - Raphadu, Thato Tshepo (My University, 2023)
Background: Hypertension (HT) and obesity have both been on the rise in children. Each is associated with an increase in cardiovascular disease risk and both track into adulthood. Objectives: Hence, this study aimed to identify the association of sodium intake (Na), potassium (K) intake, and sodium-to-potassium (Na/K) ratio with the development of HT and abdominal obesity amongst the Ellisras rural population over time. Methods: In this longitudinal study, data on dietary intake of Na and K were collected using a 24-h recall questionnaire from a total of 325 participants tracking them from 1999 (5–12 years), 2001 (7–14 years) and 2015 (18–30 years). Blood pressure (BP) and anthropometric measurements [waist circumference (WC) and height] Parametric (independent t-test) and Chi-square/Fishers’ exact tests were conducted to determine the difference between the years for numerical data and categorical variables. A generalized estimating equation (GEE) was conducted to assess the association of Na intake, K intake; and their ratio on BP, WC and WHtR. Results: Our results indicate a significant positive association between K intake and WHtR [β= 0.019, (95% CL: 0.004, 0.034) p-value= 0.012], and even the model was adjusted for age and sex there was still an association with WHtR. Na/K ratio was associated with SBP [β= 4.326, (95% CL: 2.056, 6.595) p-value= < 0.001], DBP [β= 2.028, (95% CL: 0.703, 3.353) p-value= 0.003], WC [β= 4.191, (95% CL: 2.080, 6.302) p-value= < 0.001] and WHtR [β= 0.014, (95% CL: 0.003, 0.026) p-value= 0.015], respectively. Furthermore, Na/K was shown to be associated with an increased risk of developing HT [Exp = 1.603, (95% CL: 1.164, 2.207) p-value= 0.004] and abdominal obesity [Exp = 1.797, (95% CL: 1.207, 2.677) p-value= 0.004]. Conclusion: In our study we observed that an increase in Na/K it’s a predictor of HT and abdominal obesity over time compared to Na and K alone. However, more studies are required to further prove this.
Thesis (M.Sc. (Physiology)) -- University of Limpopo, 2023
Keywords: Hypertension; Cardiovascular disease; Abdominal obesity; Sodium; Potassium; Longitudinal study; Hypertension; Obesity; Sodium; Sodium -- Physiological effect; Potassium